Limbah Cangkang Telur sebagi Lukisan Kaligrafi - Mazidatul Faizah; Faiqotul Himmah; Lailatul Fitriyah; Nur Aini Solikhah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
There is a lot of shell waste in the environment. In the village of Tampingmojo, there is also a lot of eggshell waste produced from household waste. The need for an idea to use it into something useful is to make it a craft that has a high selling value and can protect the environment from waste. The method used in the implementation of this community service activity is the Asset Based Community Development (ABCD) method. This method has five steps, namely as follows: 1) Discovery, 2) Dream, 3) Design, 4) Define, 5) Destiny. As a result, egg shells can be used to make calligraphy so that waste that previously had no economic value becomes valuable and has economic value to increase income.